Pengaruh Pelayanan Fiskus, Persepsi Atas Efektivitas Sistem Perpajakan, Pengetahuan Pajak, Dan Kesadaran Wajib Pajak Terhadap Kepatuhan Wajib Pajak Orang Pribadi: Studi Di KPP Pratama Tigaraksa - Melando, Nelinda; Waluyo, Waluyo (Universitas Multimedia Nusantara, 2013)
This research aims to analyze the impact of tax service, perception of effective tax system, knowledge of tax, and awareness of taxpayers towards individual taxpayers compliance, as well as to obtain empirical evidence on research conducted either empirically or simultaneously. The research method used is a causal study. Causal study means that the researchers wanted to examine the relationship between independent variables with dependent variable. The populations of research was all individual taxpayers registered in the tax office (KPP) Pratama Tigaraksa. The sample of population used is individual taxpayer who enrolled in KPP Tigaraksa especially in Kelapa Dua subdistrict at period 2012. Sample was used 102 respondence. These results indicate that variable tax service have signigicant effect towards individual taxpayer compliance, variable perception of effective tax system didn't have significant effect towards individual taxpayer compliance, knowledge of tax have significant effect on individual taxpayer compliance, and awareness of individual taxpayers have significant effect on individual taxpayer compliance. Keywords: Tax Service, Perception of Effective Tax System, Knowledge of Tax, Awareness of Individual Taxpayers and Tax Compliance